Characterization of mitochondrial proteins in Trypanosoma brucei - Svoboda, Lucia (Jihočeská univerzita, 2018)
In this thesis proteins Tb927.2.3030 and Tb927.11.4870 are localized by in-situ tagging, im-munofluorescence microscopy and cell fractionation. Their essentiality for growth is deter-mined by downregulation with RNA interference.
Characterization of mitochondrial proteins in Trypanosoma brucei